Pengaruh Desain Produk dan Promosi terhadap Keputusan Pembelian Produk RC Feat RB Bordir - Ninda Nadia (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2022)
This study aims to determine the effect of product design and promotion on purchasing decisions for RC Feat RB Embroidery Products (a Survey of RC Feat RB Embroidery Consumers). The method used is a quantitative approach with the survey method. With a research sample of 100 consumers RC feat RB Embroidery. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 26.0. The results showed that the product design perceived by consumers of RC feat RB Embroidery had very good criteria. The promotion of the RC feat RB Embroidery had very good criteria. Purchasing decisions on consumers of RC feat RB Embroidery have good criteria. Simultaneously product design and promotion have a significant influence on purchasing decisions. Partially Product Design has a significant influence on purchasing decisions. Partially Promotion has a significant effect on purchasing decisions.